Análisis psicométrico del Inventario de Estrategias de Aprendizaje y Estudio en estudiantes universitarios de psicología de Lima metropolitana - Escurra Mayaute, Luis Miguel (2006)
This is a methodological investigation of the validity and reliability of the Inventory of Learning and Study Strategies Inventory (LASSI). The simple descriptive design was applied to 566 university students of psychology in metropolitan Lima, using a multi-phased stratified sample. The comparative analysis indicated that students of private universities showed better performance than students from public universities in the scales of Attitude, Motivation and Self-Testing. Differences by sex in the scales of Attitude, Time Management, Anxiety and Study Aids were observed.